2018
DOI: 10.1002/cncr.31572
|View full text |Cite
|
Sign up to set email alerts
|

Putting the life in lifestyle: Lifestyle choices after a diagnosis of cancer predicts overall survival

Abstract: Greater dissemination and implementation of effective interventions to reduce alcohol use and increase physical activity in cancer patients are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 65 publications
1
10
0
3
Order By: Relevance
“…Data are also available to suggest that optimism can be eroded by events that are very negative in nature. For example, one study tracked the change in optimism that occurred during the 18-month period following diagnosis for advanced stage cancer involving the hepatobiliary-pancreatric system (Krane, Terhorst, Bovbjerg, Scheier, Kuicinski et al, in press). They found that levels of optimism declined slightly, but significantly, over the time period studied.…”
Section: Stability Of Optimismmentioning
confidence: 99%
See 3 more Smart Citations
“…Data are also available to suggest that optimism can be eroded by events that are very negative in nature. For example, one study tracked the change in optimism that occurred during the 18-month period following diagnosis for advanced stage cancer involving the hepatobiliary-pancreatric system (Krane, Terhorst, Bovbjerg, Scheier, Kuicinski et al, in press). They found that levels of optimism declined slightly, but significantly, over the time period studied.…”
Section: Stability Of Optimismmentioning
confidence: 99%
“…Clearly, not every study produces positive findings. For example, sometimes an association is found for cancer-specific mortality (Kim et al, 2016) and sometimes not (Krane et al, in press; Tindle et al 2009). Variations and inconsistency do exist.…”
Section: Effects Of Dispositional Optimism On Physical Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…Comportamientos saludables entre ellos hábitos de dieta y actividad física se han relacionado en la prevención del cáncer, no obstante, son pocos los estudios que se enfocan a estudiar los El exceso de grasa corporal, especialmente con aumento del perímetro de cintura, ocasionado por una alteración en el balance calórico, induce al aumento de citocinas proinflamatorias, que a su vez incrementan el riesgo de padecer enfermedades crónicas como el cáncer cambios de salud después del primer diagnóstico de la enfermedad. Aunque los cambios relacionados con comportamientos en salud pueden ocurrir sin intervención y son más frecuentes después de un diagnóstico de cáncer, son conductas modificables y por tanto su comprensión por parte de las personas con recidivas o en prevención primaria incluso, pueden facilitar intervenciones efectivas que contribuyan al control o progresión de la enfermedad 10 . Muchos cambios dependen de la actitud que presenten las personas frente al diagnóstico de la enfermedad y se ha estudiado como individuos más optimistas con diagnósticos de cáncer, mejoran el tiempo dedicado a la actividad física, incrementan el consumo de frutas y verduras y disminuyen la ingesta de alcohol y de cigarrillo; es de anotar como una dieta saludable se asocia a menores síntomas depresivos 10 .…”
Section: Introductionunclassified